Variations of Productive Waqf Management Model in Indonesia: A Literature Study - Lathif, Sirajuddin (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2024)
This research examines different productive waqf management models in Indonesia. The study used a qualitative approach, focusing on literature. The findings revealed that the most commonly-implemented productive waqf management model was the productive investment one, which involved land and building rentals. In second place was the profit-sharing financing model, which included collaborations with third parties such as cooperatives, outsourcers, and other institutions. The study also identified the social infrastructure development model, by which buildings such as schools and places of worship were built. The variations in productive waqf management models in Indonesia, as found in this study, were still relatively low when compared to the strategic productive waqf land categorization compiled by the Directorate of Waqf Empowerment. This highlights the need for the Indonesian Waqf Board to develop strategies to increase the ratio of productive waqf at national and sub-national levels, which will eventually lead to the rise of the National Waqf Index.